An unusual presentation of dystonia and chorea from intraventricular pneumocephalus - Polster, Sean P. (Surg Neurol Int, 2018)
BACKGROUND: Pneumocephalus is a common finding following intracranial procedures, typically asymptomatic and resolves within several days. However, in some cases, pneumocephalus presents with headache, encephalopathy, or symptoms of elevated intracranial pressure. Here, we present a case of iatrogenic tension pneumocephalus following endoscopic sinus surgery, presenting as abnormal involuntary movements resembling a movement disorder with choreiform movements. CASE DESCRIPTION: A 67-year-old previously healthy male presented with new onset chorea and dystonia associated with headache, encephalopathy, and postural instability 4 days after undergoing endoscopic sinus surgery for chronic sinusitis and nasal polyps. Computed tomography showed prominent intraventricular pneumocephalus causing enlargement of the anterior horns of both lateral ventricles with lateral displacement of the basal ganglia nuclei and a bony defect in the skull base. Neurosurgical correction of the cranial defect provided complete symptomatic resolution. Pneumocephalus as a result of an iatrogenic injury of the skull base manifesting as an acute movement disorder is a rare complication of a nasal sinus procedure. We speculate that compression of the caudate nucleus and striatum resulted in decreased pallidothalamic inhibition and thalamocortical disinhibition leading to the development of a hyperkinetic movement disorder. CONCLUSION: This unusual presentation of a common procedure illustrates a neurological emergency that requires prompt recognition and timely correction.